Investigation of Challenges in Pronouncing English Words Among Banyumasan Speakers - Titis Yekti Lestari; Irma Fajar Tri Utami; Merie Dreana Kamelia Rosyta ((JELE) Journal Of English Language and Education, 2023)
The difference in the pronunciation of English words by the Banyumasan people with English standards is fascinating. This happens because of the uniqueness of the Banyumas dialect. This research aims to describe the various errors, the frequency of errors occurring, and the factors that are thought to cause errors made by respondents from Banyumasan in English pronunciation. The subjects of this research were people who used the Banyumasan dialect, and the sample for this research was 15 people. In this research, the researchers used a qualitative descriptive method. Data collection was also carried out using questionnaires and voice recordings. The researchers analyzed the data using the matching method. The frequency of errors made between the pronunciation of consonants, vowels, and diphthongs that often occur include errors in the pronunciation of the consonant /d/ around (60%) and in the pronunciation of the consonant /g/ around (47%), consonant /b / around (20%), vowel /ɛ/ around (53%), vowel /ɪ/ as much as (47%), and finally the pronunciation of the diphthong /eɪ/ around (60%). Factors that cause errors include mother tongue interference, habits, and input errors, resulting in respondents' lack of understanding of English language rules.